Diabetes and the prostate - Sanjay Kalra; Nitin Kapoor; Saurabh Arora (Journal of the Pakistan Medical Association, 2023)
Here we discuss the interactions between prostatic health and diabetes. Diabetes may be associated with changes in prostatic anatomy, physiology, clinical morbidity, and clinical outcomes. Certain glucose-lowering drugs may impact prostatic health, and some prostato-tropic medications can influence glycaemic control. One should be vigilant for symptoms and signs of prostate health in diabetes. Keywords: benign prostatic hyperplasia, erectile dysfunction, male gonad, male reproductive health, metformin, prostatic cancer, SGLT2i.